The acute effect of a sport-specific stretching routine on the performance of vertical jumps in rhythmic gymnasts - Silva, G. F.; Almeida, A. R.; Rodrigues, S. A.; Szmuchrowski, L. A.; Silva, R. A. D.; Drummond, M. D. M. (Journal of Exercise Physiology online, 2018)
The purpose of this study was to investigate the acute effect of a specific flexibility training session on the height of a countermovement jump (CMJ) in Rhythmic Gymnastics (RG) Athletes. The subjects in this study were 13 female athletes with a mean age of 14.5 ± 2.43 yrs. After familiarization with the CMJ, the subjects performed the two evaluation sessions with a 48-hr interval between the two sessions. The athletes performed the CMJ tests without and with a predetermined stretch routine, which had pre-defined parameters specific to the modality. The results demonstrated a significant reduction in the height of the vertical jumps in the second session, compared to the first session (P=0.0001). Therefore, the modality-specific stretching protocol that was used generated an acute negative effect on the athletes` CMJ performance.